The Influence of Content Marketing, Influencer Marketing, and Live Streaming on Impulsive Behavior in Generation Z on TikTok Shop E-Commerce - Diansyah, Diansyah; Rachmawati, Syarah (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of Content Marketing, Influencer Marketing, and Live Streaming on the impulsive behavior of Generation Z in shopping for fashion products on the TikTok Shop platform. This study uses a quantitative approach with a survey method, namely by distributing questionnaires to respondents who belong to Generation Z and have made purchases on TikTok Shop. To take samples, the researcher used purposive sampling, while to analyze the data, multiple linear regression analysis was used with the help of SPSS software. The results show that separately, Influencer Marketing and Live Streaming have a positive and significant effect on impulsive behavior, while Content Marketing does not have a significant effect. In addition, Live Streaming is the main factor that influences buyers' impulsive behavior. Concurrently, the three variables, namely Content Marketing, Influencer Marketing, and Live Streaming, had a significant effect on the impulsive behavior of Generation Z. These findings indicate that digital marketing strategies, especially interactive Live Streaming and the use of trusted influencers, can increase consumers' impulsive purchasing decisions on social media-based e-commerce platforms.